The relation between Austrian School Economic Method and Liberalism - Slatinsky, Rafael; Matos Faria, Diane (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2024)
Abstract: This article explores the interconnection between the aprioristic method of the Austrian School and classical liberal thought in economics. Initially, it examines the origin of liberalism and classical economics, studying the ideas of John Locke and Adam Smith, respectively. Subsequently, the relationship between liberalism and neoclassical economics is analyzed, presenting the Marginal Value Theory and highlighting the convergences and distinctions in relation to the thought of the Austrian School. In this context, Austrian thought is presented with the insights of Mises, particularly with his concept of praxeology, and Friedrich Hayek, with his critiques of orthodox thought. Finally, considering the perspective of various economists and the interdisciplinary approach of economic science, it is concluded that the Austrian School, in conjunction with classical liberalism, offers an appropriate interpretation of societal reality.